2014
DOI: 10.3389/fnbeh.2014.00135
|View full text |Cite
|
Sign up to set email alerts
|

Mood disorders in Huntington's disease: from behavior to cellular and molecular mechanisms

Abstract: Huntington's disease (HD) is a neurodegenerative disorder that is best known for its effect on motor control. Mood disturbances such as depression, anxiety, and irritability also have a high prevalence in patients with HD, and often start before the onset of motor symptoms. Various rodent models of HD recapitulate the anxiety/depressive behavior seen in patients. HD is caused by an expanded polyglutamine stretch in the N-terminal part of a 350 kDa protein called huntingtin (HTT). HTT is ubiquitously expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 175 publications
(256 reference statements)
1
63
1
Order By: Relevance
“…The current findings of no observed sex differences in distress is also inconsistent with the trend for sexual dimorphism found in mice models with HD [19]. One body of research has identified depression to be associated with altered hypothalamic-pituitary-19 adrenal (HPA)-axis functioning (44)(45)(46)(47), and these mechanisms have been proposed for sex differences in depressive behaviours in rodents [48].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The current findings of no observed sex differences in distress is also inconsistent with the trend for sexual dimorphism found in mice models with HD [19]. One body of research has identified depression to be associated with altered hypothalamic-pituitary-19 adrenal (HPA)-axis functioning (44)(45)(46)(47), and these mechanisms have been proposed for sex differences in depressive behaviours in rodents [48].…”
Section: Discussioncontrasting
confidence: 73%
“…Of the limited human studies available, there is evidence to suggest that the usual ratio of discrepancy noted between men and women does not exist in HD [9,18]. More research regarding sex differences in anxiety and depressive-like behaviours in HD has been undertaken using various mice models [19]. Animal models of HD enable researchers to consider the aetiology of behavioural symptoms and also mechanisms underlying sex differences, as potential biological contributions can be tested in the absence 6 of psychosocial issues affecting human gene carriers, such as the knowledge that they have a fatal neurodegenerative condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is a common comorbidity in neurodegenerative disorders, such as Parkinson’s disease (PD) [10] and Huntington’s disease (HD) [11], and is thought to arise from neurodegeneration in the depression-related brain circuitry in these disorders. Depressive symptoms could even precede the motor impairment in PD and HD, arguing against that depression merely results from motor disability.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a strong association between MDD and HD [93]. In addition, the incidence of suicide is higher in patients with HD than the general population; this association has been attributed to physiological degeneration [94].…”
Section: Major Depressive Disorder (Mdd) and Huntington Disease (Hd)mentioning
confidence: 98%